THE FUTURE OF KUDUS AS A RELIGIOUS CITY IN CENTRAL JAVA - Wijaya, Muhammad Indra Hadi; Puspasari, Deny Aditya; Ariani, Nofa Martina; Susanti, Retno; Ichsanudin, Habib (Jurnal Pengembangan Kota, 2023)
Urban planning is needed to manage changes within a spatial approach. It helps in planning activities where the economic, environmental, and social goals are holistically managed. The planning process involves studying past trends, learning from past and present, and preparing for the future. The fast development and adoption of new cultures lead to significant changes in socio-cultural and economic growth. Some Industry activities, especially religious ones in this decade, brought many changes in Kudus, Central Java, and Indonesia. It diversifies the city's social and cultural identity and generates tremendous economic development opportunities. Therefore, the town has several potentials facing urban planning problems. Exploring these issues and the reasons behind them will help minimize their impact. Kudus has tremendous potential for research in this direction. The need of the decade for urban planners and designers is to be prepared for the changes in a Kudus city. This study identifies the growth of Kudus as a religious city along with changes in regional spatial plans using descriptive qualitative analysis from secondary data such as planning documents and primary data from in-depth interviews with relevant stakeholders. This study shows Kudus as a religious city having challenges of spatial changes and growth patterns of religious tourism growth in the Kudus area.